Crystallization and preliminary X-ray diffraction studies of a deglycosylated glucose oxidase from Penicillium amagasakiense - Hendle, Jörg; Hecht, Hans-Jürgen; Kalisz, Henryk M.; Schmid, Rolf D.; Schomburg, Dietmar (Journal of molecular biology, 1992)
The dimeric glucose oxidase from Penicillium amagasakiense was deglycosylated, purified and crystallized as a complex with its coenzyme FAD. Deglycosylation and purification to isoelectric homogeneity were shown to be an important prerequisite step to obtain crystals suitable for X-ray investigations. Crystals of the deglycosylated enzyme were reproducibly grown using ammonium sulfate as precipitant at pH 7.4 to 7.5. Crystals diffract to at least 2.0 Å resolution and belong to the orthorhombic space group P2 12 12 1, with refined lattice constants of a = 59.3 A ̊ , b = 136.3 A ̊ and c = 156.7 A ̊ . Assuming two monomers (≈ 135 kDa) per asymmetric unit the V m value is 2.3 Å 3/Da.